Contemporary confessional writing between historiography and biography (preliminary notes on the manuscript “Sacred faith. The book of life and sufferings of the Old Believers of Sym”) - Prigarin, Aleksandr Anatolyevich; Storozhenko, Alena Aleksandrovna; Tatarintseva, Margarita Petrovna (The New Research of Tuva, 2020)
The article examines the manuscript of the book “Sacred faith. The book of life and sufferings of the Old Believers of Sym” written by N. G. Sidorkina (Golovko). Although created at the very beginning of 21st century (2002), the text deals with the complex history of life and isolation Titovtsy (a group of Old Believers) experienced in the 20th century, especially along the Middle Yenisei. The authors examine the manuscript as an original work by a contemporary Old Believer. The article focuses on the Old Believers of the Titov accord living along the “Yenisei Meridian”, a unified confessional space of the Chasovennoye accord which includes the Krasnoyarsk territory and Tuva, and on these people’s authentic worldview. The authors study how the manuscript was created, as well as its content. Its uniqueness is due to the “internal dialogue” and autoethnographic reflection. The preliminary analysis of the text’s sources, and the use of expedition methods of textual study, helped both demonstrate the authenticity of the manuscript and describe its importance for the current historiography of the Old Belief. It is significant that the researcher herself, using her field experience, turned her life into a continuous study of a distinctive group of Old Believers. The article also examines the expressive genre of the manuscript, which contributes to the “Old Believer writing” as a cultural phenomenon and reveals its structural and semantic features. According to the Sidorkina’s concept, the manuscript is equally focused on both confessional and general literacy. This “double” erudition and active appeal to both worldviews have mutually determined further development of Old Believer thought.